Saberes e fazeres no extrativismo do açaí da Comunidade Quilombola de Santa Quitéria e Itacoâzinho, Acará - PÁ - SILVA, Ailton da Conceição (2025)
This research aimed to identify and value the knowledge and practices associated with açaí extraction in the remaining quilombola communities of Santa Quitéria and Itacoãzinho, in the municipality of Acará, Pará. Açaí is the main product for extractivists, which guarantees food and nutritional sovereignty and social and economic strengthening of families, based on the common good, respect for nature and working in a sustainable manner, with transparency with the community. Through this work, it was observed the potential of the community to work in the management of açaí in a traditional way. Even without the support of technical assistance, it manages to produce a healthy product, with good productivity, recognized within and outside the community. Some weaknesses were addressed, such as the difficulties in accessing new markets to increase yield, aspects that indicate the need for continued studies and partnerships in the community.